Intergenerational Gaps: Collaborative Projects for Social Studies Curricula (Global Journal of Human-Social Science, 2015)
The purpose of this research is to investigate whether this collaborative intergenerational project can be a bridge between seniors from rural areas and students who were raised in a nuclear family. The following questions guided this research: Can seniors' participation in photography activities help to build intergenerational solidarity between seniors and elementary school students? Can the collaborative program between seniors and elementary school students serve as a useful tool for the students' social studies classes? Can the collaborative program between seniors and elementary school students affect the students' attitudes towards seniors? What kinds of learning opportunities can this provide the participants? The overall goal of the project was to examine if we could establish a meaningful relationship between rural seniors and urban elementary school students, and to see how such a project could help connect schools and broader societies.
Keywords: generation gap; community-based research; senior center; elderly; social studies; elementary school; collaborative program; self-esteem; intergenerati